IMPLEMENTASI PERATURAN PRESIDEN (PP) NO. 72 TAHUN 2021 TENTANG PERCEPATAN PENURUNAN STUNTING PERSPEKTIF SIYASAH: (Studi Dinas Kesehatan Kab. Wajo) - Cendrakasih, Andi Asfiyanti; Basri, Halimah; Halimang, St. (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2025)
This research aims to describe the implementation of Presidential Regulation (PP) no. 72 of 2021 concerning the Acceleration of Reducing Stunting from Siyasah Dusturiyah Perspective (Study of the Wajo District Health Service). In answering this problem, the author uses a normative syar'i approach and an empirical juridical approach. The data collection methods were carried out by means of interviews, observation, documentation and literature study. The research results show that the implementation of Presidential Regulation (PP) no. 72 of 2021 concerning the Acceleration of Reducing Stunting in Wajo Regency has been going well where the Wajo district health office continues to strive to implement the program to accelerate stunting reduction. They distribute blood supplement tablets, get immunizations, get additional food, provide breast milk until the age of 24 months, get worm medicine , providing complete basic immunization to children, fulfilling nutritional needs since pregnancy, 1000 HPK, fostering exclusive breastfeeding for 0-6 months and healthy environmental sanitation. Siyasah Dusturiyah's Views on the Implementation of Presidential Regulation (PP) no. 72 of 2021 concerning the Acceleration of Stunting Reduction, in essence it does not conflict with the principles of Siyasah Dusturiyah. In essence, it is intended to enforce regulations for the benefit of its people from the regulations and policies made by its leaders. Of course, effective provisions are needed to regulate their respective duties.